Electromyography and Metabolic Myopathies - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at the Mayo Clinic, Rochester, MN, report the sensitivity and specificity of the pediatric EMG in the diagnosis of myopathic disorders in patients <18 years referred between 2009 and 2013.